(untitled) (Research, Society and Development, 2021)
Chemotherapy drugs and radiotherapy in the head and neck region are considered possible to interfere with odontogenesis. Patients may present alterations such as tooth agenesis, shortening or root malformation, enamel hypoplasia and microdontia. Such effects do not occur in adults, as they already have the dental structures formed. The objective of this study is to describe, through a case report, the dental alterations and implications for the clinical practice of a patient who received chemotherapy and radiotherapy in childhood. A 12- year-old female patient was diagnosed with embryonal rhabdomyosarcoma in the right parotid gland region at 5 years of age. Antineoplastic treatment consisted of IRS IV chemotherapy protocol: ifosfamide (IFO) - doxorubicin (DOXO) - etoposide (VP16) followed by vincristine - dactinomycin - cyclophosphamide (VAC) / vincristine - ifosfamide - etoposide (VIE) alternated, in addition to conventional radiotherapy, with a total dose of 45 Gy. The patient developed important dental alterations, such as root malformation in most teeth, microdontia and enamel hypoplasia, being essential the role of the dentist. Currently, after 6 years of anticancer treatment, she has regular dental follow-up.